Nanomaterials in drug delivery system - Mohd Razali, Nur Izzati; Mohd Saufi, Noor Syazwani; Ahmad Raus, Raha; Wan Nawawi, Wan Mohd Fazli; Basri, Dayang Fredalina (Springer, 2019)
In this article, nanomaterials that are currently being investigated for their potentials in biomedical field and have established to be drug carriers are elaborated. Liposome for example, has already been utilised in biomedical applications for a long time ago but extensive studies are still conducted in order to optimize its properties for better results. Each nanomaterials discussed in this article exhibits unique physiochemical and biological characteristics which give them flexibility to be used in many applications. Some exist as natural nanomaterials such as liposome, while some can be synthesized from certain compounds. Some nanomaterials can be functionalized to enhance their efficiency as drug carriers. However, not all synthetic nanomaterials are safe to be consumed by human. Therefore, further investigations and evaluations of each nanomaterial in term of long term effect in vivo must be carried out.